EFFECTS OF AVOIDANCE UNDER THE UNITED NATIONS CONVENTION ON CONTRACTS FOR THE INTERNATIONAL SALE OF GOODS - 1980 (مجلة أبحاث قانونية, 2023)
ABSTRACTThe completion of this study requires extensive information gathering and research.In order to address the main research question effectively, this study will be relied on both analytical and critical methods. The focus of the analysis will be on the UN convention on contracts for the international sale of goods and its prospects for the effect of avoidance of the contract. This approach requires the assessment of both the positive and negative sides in this convention.Finally, this topic has been subjected to development and codification by some scholars. Which means that the documents relating to these scholars on international sale of goods offer a wealth of information and often lead to a variety of response from scholars, which it will be an important resource in my work.
Keywords: INTERNATIONAL SALE OF GOODS; DECLARE OF AVOIDANCE; EFFECT OF AVOIDANCE; SUBSTITUTE TRANSACTION RULE; THE MARKET-PRICE RULE